Analisis Interaksi Teman Sebaya Dan Kemandirian Belajar Mahasiswa - Ashabul Kahfi (Institut Binamadani Indonesia, 2019)
Peer interaction is a friend relationship in the same time relative to working together, talking to each other, discussing to achieve certain goals. Learning independence is one's ability to realize the desire to learn with others. Different, able to do their own learning, can determine effective ways of learning,are able to do learning tasks well and are able to learn independently. The purpose of this study was to determine the effect of students and students. The method used is descriptive quantitative method with data collection techniques: interviews, questionnaires, library data and data analysis which are descriptivestatistical analysis. The conclusion of this study is that the peers are categorized enough, with an average score of 41.2. While students' self-reliance is included inenough categories, with an average score of 43.2.Keyword: Interaction, Peer Friends, Learning Independence.